2010
DOI: 10.3126/jowe.v3i0.2222
|View full text |Cite
|
Sign up to set email alerts
|

Fractionation of Trace Metals between Catchment Soils and Associated Wetland Sediments of Selected Wetlands of Lake Victoria, East Africa

Abstract: The aim of this work was to study the trace metals transfer between soil aquifers and the immediate sediments of the selected wetlands of Lake Victoria. The study covered five trace metals Pb, Cd, Cu, Zn and Mn as these are associated with vehicular traffic and with the combustion of fossil fuels which could both be significant sources of pollution within the wetlands of Lake Victoria basin. Three types of trace metal analyses from various locations of Katonga, Simiyu and Nyando catchments of Lake Victoria wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
1

Year Published

2012
2012
2016
2016

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
3
1
Order By: Relevance
“…The spatial distributions of Cu and Pb concentrations in sediment were unregularly. Except for Cd at site T04 and N04, the total contents of heavy metals were clearly higher in soils than associated sediments, which was different from the study of Lake Victoria [29]. It may be that the movement of water washed out the top sediments which resulted in a higher concentration in soils than in sediments.…”
Section: Resultscontrasting
confidence: 73%
“…The spatial distributions of Cu and Pb concentrations in sediment were unregularly. Except for Cd at site T04 and N04, the total contents of heavy metals were clearly higher in soils than associated sediments, which was different from the study of Lake Victoria [29]. It may be that the movement of water washed out the top sediments which resulted in a higher concentration in soils than in sediments.…”
Section: Resultscontrasting
confidence: 73%
“…High nutrient inputs have increased eutrophication levels [8][9][10] and also that algae biomass has increased causing the lake bottom waters to be more anoxic [11,12]. Heavy metal pollutants are threatening the wetland environment of Lake Victoria are trace elements [13][14][15]. These pollutants especially lead have been associated to increased shipping traffic, car washing and discharge from local industries [16,17].…”
Section: Introductionmentioning
confidence: 99%
“…Soil characteristics and the leaching capacity of the nutrients Extraction of the samples by 0.4 HCl and 1.0 M NH 4 CH 3 COO consecutively, indicated that the higher fraction of the soils around Simiyu are contained in the residual fraction Pb (100%), Cd (24%), Cu (18%), Zn (26%) and Mn (31%), respectively (Henry and Omutange 2009). In sediments the residual fractions contained Pb (36%), Cd (27%), Cu (18%), Zn (26%) and Mn (51%), respectively.…”
Section: Distribution Of Cr Pb Zn Cu and Mn In Soilsmentioning
confidence: 99%
“…The pollutants are partly filtered by the soils, sediments and the plants but some of the pollutants eventually enter the lake (Makundi 2001). Among the pollutants that are threatening the wetland environment of Lake Victoria are trace elements (Nabulo et al 2008;Henry and Omutange 2009;. Trace elements are toxic to living organisms including human being when present at higher concentration than required for normal growth; they can be accumulated through food chain system.…”
Section: Introductionmentioning
confidence: 99%